Pengaruh Pemberian Omega-3, Omega-6, dan Kolesterol Sintetis terhadap Kualitas Reproduksi Burung Puyuh Jantan - Isnaeni, Wiwi; Fitriyah, Abyadul; Setiati, Ning (Biosaintifika: Journal of Biology & Biology Education, 2010)
The aims of this research were to study the effect of using the omega-3 (O-3), omega-6(O-6), and synthetic cholesterol (Ch) on the reproductive quality of the male quails.Samples of this research were 35 of 4 weeks old male quails with 60 to 98 g of weight.The samples were grouped randomly into 7 groups, that are R-0 (control-group), R-1(0,163 mg O-3/100 g body weight), R-2 (0,326 mg O-3/100 g bw), R-3 (0,163 mgO-6/100 gbw), R-4 (0,326 mg O6/100 g bw), R-5 (20 mg Ch/100 g bw), and R-6 (40mg Ch/100 g bw). The treatment was given per oral in three periods with 5 days ofeach. there was a week intervening between periods. During the research, samples weregifted rations a basalic-woof (basalic-feed) for twice/day, at 7:00 and 16:00 oâclock. theamount of basalic-woof were 20 g of feed/100 g body weight/day. Water administeredin an ad libitum manner. This research was implemented during 8 weeks. The variableswere the level of testosterone, blood qualities, voice-qualities, color brightness of chestfur, and testis size. The voice quality data were analyzed by one-way ANOVA continuedby orthogonal contrast test. The other data were analyzed by descriptive statistic. Theresult of this research confi rmed that synthetic omega-3 and omega-6 (0,326 mg/100 gbw) and synthetic cholesterol (20 mg/100 g bw) could increase the reproductive qualityof the male quails.Keywords: synthetic cholesterol, synthetic omega-3, synthetic omega-6,reproductive quality